Regional poverty and population response. A comparison of three regions in the United States and Germany. - Siebert, Rosemarie; Singelmann, Joachim (Bundesinstitut für Bevölkerungsforschung, 2015)
In this paper, we examine poverty in three regions in the United States and Germany and discuss its causes and demographic consequences. The three regions are those with the highest rates of poverty in the two countries: the Mississippi Delta and Texas Borderland in the United States and the Northeastern Border Region in Germany. We show that standard models to explain poverty need to be placed in the historical legacies of the three regions in order to understand their current levels of poverty. While our results show many common factors for poverty in the three regions, they also point to important differences. Similarly, we identify differences among the regions in their demographic responses to poverty, in part reflecting their different historical legacies. Thus, one implication of the paper is the importance of place-based poverty-mitigation strategies for successful policy planning.
Keywords: Armut; Regionale Disparität